2020
DOI: 10.1080/03461238.2020.1814855
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy and lifespan disparity forecasting: a long short-term memory approach

Abstract: After the World War II, developed countries experienced a constant decline in mortality. As a result, life expectancy has never stopped increasing, despite an evident deceleration in developed countries, e.g. England, USA and Denmark. In this paper, we propose a new approach for forecasting life expectancy and lifespan disparity based on the recurrent neural networks with a long short-term memory. This type of neural network leads to predicting future values of longevity indexes while maintaining the significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…For instance, Aburto and colleagues ( 2020 ) showed that the association was stronger when mortality reduction occurred more at younger ages, and weaker when mortality improvement was more observed at older ages. Nigri and colleagues ( 2021a , 2021b ) found that the strength of this association is related to the location and speed when a country moves along the life expectancy distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Aburto and colleagues ( 2020 ) showed that the association was stronger when mortality reduction occurred more at younger ages, and weaker when mortality improvement was more observed at older ages. Nigri and colleagues ( 2021a , 2021b ) found that the strength of this association is related to the location and speed when a country moves along the life expectancy distribution.…”
Section: Introductionmentioning
confidence: 99%
“…This is a question with important theoretical and practical implications. From a theoretical perspective, studying the relationship between average longevity and lifespan variability is fundamental for a proper understanding of the dynamics in human mortality, and is crucial for forecasting future patterns of population health (see related work by Bohk-Ewald et al, 2017 ; Nigri et al, 2021a , 2021b ; Rabbi & Mazzuco, 2021 ). From a practical and policy-making perspective, it is very important to know whether and to what extent the normatively desirable goals of increasing longevity and reducing lifespan variability can be achieved simultaneously or if one can only be attained to the detriment of the other (Benach et al, 2011 , 2013 ; Smits & Monden, 2009 ; Vaupel et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…We exploit the LSTM network endorsing an autoregressive approach on 1-minute basis. We refer the reader to Nigri et al (2020) for more technical and theoretical details related to the LSTM network.…”
Section: Btc Price Forecastingmentioning
confidence: 99%
“…( 2018 ), Nigri et al. ( 2020 )). To the best of our knowledge, our study is the first attempt to apply an indirect estimation model to address the issue of describing the mortality pattern by causes of death.…”
Section: Introductionmentioning
confidence: 98%